Penataan Perumahan Kumuh di Perkotaan Berbasis Kawasan - Noegroho, Noegi (Bina Nusantara University, 2010)
Cities in Indonesia has the same problem in the presence of slum residential in some area. The existence keeps growing altogether with the increasing of population and urbanisation in some cities. Slum residential brings several bad effects towards urban life, not only based on physical performance but also affects the decreasing in human resource quality especially those who live in the area. Along with the city development, slum residential should be arranged into a livable environment; which could be handled by area-based that placed the slum area arranged altogether by supervising surrounded environment like a united area.